Long-term effects of early environment on the brain: Lesson from rodent models. (May 2018) - Di Segni, Matteo; Andolina, Diego; Ventura, Rossella
Abstract: The postnatal period is characterized by extensive neuronal plasticity, synaptic organization, and remodeling. High neuroplasticity renders the brain sensitive to the remodeling effects induced by environmental factors, such as exposure to adversity, which can imprint neurochemical, neuroendocrine, morphological, and behavioral changes. Early experiences that influence developmental trajectories during maturation of the brain can have a wide range of long-lasting effects, modulating stress-coping strategies in adult life and inducing vulnerability or resilience to psychopathologies, depending on the gene × later experience interplay. Future studies will clarify how manipulation of the early environment induces these effects acting on genetic and epigenetic factors.